Autonomous demand, Harrodian instability and the supply side - Peter Skott (University of Massachusetts, Department of Economics, 2016)
A recent literature introduces autonomous demand as the driver of long-run economic growth and as a stabilizing force that tames Harrodian instability. The argument is unconvincing. The stabilizing effect is modest for plausible parameter values and, more importantly, it is questionable whether any components of aggregate demand can be viewed as autonomous in the long run. By contrast, models that include the supply side (the labor market) and/or economic policy can address Harrodian instability and produce level and growth effects that resemble those derived in the literature on autonomous demand.
Keywords: E11; E12; O41; 330; supermultiplier; Harrodian instability; Kaleckian models